Sosialisasi Dan Pelatihan Penerapan Layanan Administrasi Desa Berbasis Internet Desa Cibening Kecamatan Setu Kabupaten Bekasi - Suhardoyo Suhardoyo; A Sudrajat; Stanlay Stanlay; Roydawati Bunga Sihol (Institut Nalanda, 2023)
Villages as centers for government services to communities at the lowest levels are the main development focus on the Indonesian government's agenda. Through several studies, an online community service administration system was developed using an internet approach, carrying out activities including population administration, moving, business permits, building permits and issuing letters with ease and time. This provides a faster and more efficient impact and saves time. The methods used are literature studies related to internet technology, surveys and data collection on information technology infrastructure design that can be applied to online community services, analysis of survey data on real conditions in several community service centers, especially Cibening village and finally making online community service model from villages such as family cards, moving and reporting online. The result is an internet-based village community service administration application system utilizing technology. This application model also combines the advantages of an open-source application with a flexible system design for implementation and development needs, as well as support supported by mobile phone ownership to improve the quality of service to the community. The internet-based network structure makes it possible to go online not only between villages and communities but also villages and sub-districts and can be accessed anytime, anywhere, using mobile devices. The development of the application model is also based on the business process functions and village administration processes contained in Indonesian government regulations. It is also hoped that each model can be integrated to optimize efficiency and has been tried to be adapted to the community service system.